2020
DOI: 10.1002/ab.21922
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the Psychopathy Checklist‐Revised (PCL‐R) facet and item scores in predicting violent recidivism

Abstract: There is relatively limited research on psychopathy in non-Caucasian ethnic groups and even less on the utility of the Psychopathy Checklist-Revised (PCL-R) that focuses on PCL-R facet and item scores in predicting violent recidivism. In this study, we assessed the utility of the PCL-R in prospectively predicting violent versus nonviolent recidivism during an 11-year follow-up window. A high-risk sample of 451 incarcerated Korean male offenders was assessed on the PCL-R at baseline. A total of 445 were reconvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 37 publications
3
29
1
1
Order By: Relevance
“…Most of all, lacks in responsibility and empathy, which are facet 2 items, were the strongest predictors to identify child sex offenders from other recidivists. The utility of facet 2 and its items to predict violent and sexual crimes has been reported, even though not many studies focused on affective traits (Schimmenti et al, 2014;Sohn et al, 2020aSohn et al, , 2020bYang et al, 2010). In these studies, facet 2 and its items over other facets/items better predicted violent crimes including child sex offending than other types of crime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of all, lacks in responsibility and empathy, which are facet 2 items, were the strongest predictors to identify child sex offenders from other recidivists. The utility of facet 2 and its items to predict violent and sexual crimes has been reported, even though not many studies focused on affective traits (Schimmenti et al, 2014;Sohn et al, 2020aSohn et al, , 2020bYang et al, 2010). In these studies, facet 2 and its items over other facets/items better predicted violent crimes including child sex offending than other types of crime.…”
Section: Discussionmentioning
confidence: 99%
“…Sohn, Raine, and Lee (2020a) reported that facet 2 plays a major role (Cohen’s d = 0.53) in predicting violent recidivism and the callousness appears to be the strongest item of facet 2. In another study, facets 2 and 3 are more predictive of sexual recidivism (Sohn, Raine, & Lee, 2020b). In this study, callous/lack of empathy and failure to accept responsibility (items of facet 2) were identified as the most predictive of sexual recidivism compared to violent but nonsexual and general recidivism.…”
mentioning
confidence: 99%
“…Evidence for the role of the affective facet 2 in predicting violent crimes has been found in non-Western violent offenders (Sohn & Lee, 2021; Sohn, Raine, et al, 2020; Sohn, Reyes, et al, 2020). Korean offenders who reconvicted for violent crimes had significantly higher facet 2 scores than those who committed nonviolent crimes (Sohn, Raine, et al, 2020). Furthermore, sexual recidivists scored significantly higher on facet 2 compared to recidivists who committed homicide, robbery, burglary, and misdemeanor (Sohn & Lee, 2021).…”
Section: Psychopathy Facet and Item Scores And Instrumentalitymentioning
confidence: 99%
“…According to Hare, Factor 1 is counterintuitively more predictive of violence than Factor 2 ( Hare, 2021 ). In contrast, in a recent study of 445 Korean men incarcerated then released, Facet 2 showed the strongest effect size in predicting violent recidivism ( Sohn et al, 2019 ). Other studies found behavioral characteristics of psychopathy were more predictive of both general and violent recidivism ( Walters et al, 2008 ; Kennealy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 73%